STUDI AWAL PERUBAHAN SIFAT MAGNETIK TANAH AKIBAT PEMAKAIAN PUPUK KIMIA - HARIS, VENNY (Sainstek : Jurnal Sains dan Teknologi, 2013)
This study is conducted to identify changes in the magnetic properties of agricultural land due to the use of chemical fertilizers such as urea. Soil profile sampled in this study came from Tarab River District Tanah Datar West Sumatra. Soil sampled from the ground which has not been used as agricultural land and agricultural land that has been using chemical fertilizers. For the initial stage , the identification of changes in the magnetic properties of magnetic susceptibility measurements performed through. Measurements were performed by using two mass -specific frequencies of low and high frequencies of magnetic susceptibility ( ?LF and ?HF ). Measurement of low frequency magnetic susceptibility ( ?LF ) for soil samples that have not been used as agricultural land ranges in the range of 923.8 x 10-8 m3/kg to 1239.8 x 10-8 m3/kg. While the magnetic susceptibility values for soil samples ranged former agricultural land in the range of 546.6 10-8 m3/kg to 848.9 10-8 m3/kg. Based on the results of magnetic susceptibility measurements, its seen a decline in the value of magnetic susceptibility on former farmland soil using chemical fertilizers. Soil samples in this study is dominated by independent frequency SSD and MD grains based on the value of frequency -dependent magnetic susceptibility, c FD ( % ) were < 3 % .Key words: magnetic susceptibility, farmland, chemical fertilizers, frequency dependent magnetic susceptibility, cFD (%)